INTEROPERABILITAS APLIKASI BERBASIS WEB SERVICE - Bernard Renaldy Suteja; Rusdy Agustaf (Universitas Janabadra, 2020)
Today, the need to fill information as data is increasing rapidly. At the past, fill many forms in the format of papers. But now, the forms are changing to paperless format. This can be achieve by making an application capable of data input, edit the data, and post the data across all computing/technological platform available these days. The need for this application can communicate with each other. Related to this, there are many things needed, to achieve unlimited data transfer in various applications. One of the most important aspect that can make seamless communication/integration across applications is web service. Keywords: REST API, SOAP, Semantic